Flexible polyvinyl alcohol-polyurethane sponge as well as preparation method and application thereof

The introduction of C=C groups into polyvinyl alcohol-polyurethane sponges through the radiation crosslinking method and forming a three-dimensional crosslinking network structure is solved, which solves the shortcomings of the sponges in terms of mechanical and safety performance, and achieves the improvement of the efficient mechanical performance of the material and the combination of safety and environmental protection characteristics.

CN119775629AActive Publication Date: 2025-04-08CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510285963.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-08
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The existing polyvinyl alcohol-polyurethane sponges have shortcomings in mechanical and safety performance, and are difficult to be widely used in areas with strict requirements such as the medical field.

Method used

A flexible polyvinyl alcohol-polyurethane sponge was prepared by irradiation crosslinking method. By introducing C=C groups and irradiation crosslinking reaction, a dense three-dimensional crosslinking network structure was formed, and the degree of crosslinking was adjusted to improve mechanical properties.

Benefits of technology

It significantly improves the mechanical properties and ductility of polyvinyl alcohol-polyurethane sponges, while avoiding the use of chemical catalysts, ensuring the safety and environmental protection of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775629A_ABST
    Figure CN119775629A_ABST
Patent Text Reader

Abstract

The invention discloses flexible polyvinyl alcohol-polyurethane sponge as well as a preparation method and application thereof, relates to the technical field of polyvinyl alcohol sponge, and solves the problem that the mechanical property and the safety performance of the existing polyvinyl alcohol-polyurethane sponge are insufficient. The preparation method comprises the following steps: reacting polyethylene glycol with hexamethylene diisocyanate to obtain an isocyanate-terminated polyurethane prepolymer, further reacting the isocyanate-terminated polyurethane prepolymer with a hydrophilic chain extender dimethylolpropionic acid and hydroxyl-containing acrylate to prepare vinyl-functionalized polyurethane, and preparing a polyurethane aqueous solution; a polyvinyl alcohol aqueous solution and a polyurethane aqueous solution are mixed, and the flexible polyvinyl alcohol-polyurethane sponge is prepared after treatment of the steps of irradiation, freeze drying and the like. The polyvinyl alcohol-polyurethane sponge provided by the invention has a compact three-dimensional cross-linked network structure, is good in flexibility, adjustable in mechanical property and relatively high in water absorption, ensures the application safety of the sponge in the fields of biological medicines, tissue engineering and the like, and meets the development requirements of green materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl alcohol sponges, and in particular to a flexible polyvinyl alcohol-polyurethane sponge and a preparation method and application thereof. Background Art

[0002] As an important type of functional material, sponge materials are widely used in many fields such as industry, civil use, and medical treatment. Among them, polyvinyl alcohol sponge is a high-porosity foam material made through a foaming process. It has excellent water absorption, hygroscopicity, and biocompatibility. It is widely used in medical dressings, environmental water treatment, packaging materials, and other fields. However, polyvinyl alcohol sponge is prone to water loss, resulting in poor flexibility. Its application in the medical field may cause secondary trauma to patients, and the material is prone to rupture or deformation when subjected to high pressure or long-term use. Polyurethane sponge is a highly elastic, porous structure material made through a polyurethane foaming reaction. It has excellent elasticity and softness, can withstand multiple compressions and deformations and quickly recover to its original state. It is widely used in furniture, automobiles, construction, packaging, and medical fields, but the long-term stability and environmental friendliness of polyurethane sponge need to be improved.

[0003] At present, researchers have tried to combine polyvinyl alcohol sponge and polyurethane sponge to prepare polyvinyl alcohol-polyurethane sponge, so as to overcome the defects of polyvinyl alcohol sponge and polyurethane sponge when used alone. For example, Chinese patent document CN102827442A discloses a method for preparing a polyvinyl alcohol-polyurethane superabsorbent sponge, which uses polyvinyl alcohol and polyurethane prepolymer to crosslink and solidify, and improves its stability and mechanical properties by physical blending and foaming, but the method involves the use of toxic organic tin catalysts, and there are potential risks in the application of the medical field. Chinese patent document CN112063008A discloses a water-soluble sponge with a density gradient, a preparation method thereof, and an application thereof, which uses polyurethane and polyvinyl alcohol aqueous solution to blend, centrifuge, and freeze-dry to prepare a water-soluble sponge with a density gradient as a hemostatic material, but the mechanical properties of the water-soluble sponge prepared by the invention still need to be improved, so as to provide sufficient structural support and bearing capacity in practical applications.

[0004] In summary, the development of a flexible polyvinyl alcohol-polyurethane sponge with excellent mechanical properties and safety performance is of great significance for further broadening the application fields of sponge materials and promoting the innovative development of materials science and green technology. Summary of the invention

[0005] In order to solve the problem that the mechanical properties and safety performance of the polyvinyl alcohol-polyurethane sponge in the prior art are insufficient, the present invention provides a flexible polyvinyl alcohol-polyurethane sponge and a preparation method and application thereof.

[0006] A method for preparing a flexible polyvinyl alcohol-polyurethane sponge comprises the following steps: S1: polyethylene glycol (PEG) and hexamethylene diisocyanate (HDI) are mixed and stirred to react to obtain an isocyanate-terminated polyurethane prepolymer; S2: adding a hydrophilic chain extender dimethylol propionic acid (DMPA) to the isocyanate-terminated polyurethane prepolymer for reaction, lowering the temperature of the reaction system after the reaction is completed, continuing to add hydroxyl-containing acrylate for reaction, and finally adding triethylamine (TEA) for neutralization reaction to prepare a vinyl functionalized polyurethane, and dispersing the vinyl functionalized polyurethane into a polyurethane aqueous solution; S3: mixing the polyvinyl alcohol aqueous solution with the polyurethane aqueous solution prepared in S2, irradiating, then freeze-molding, and finally freeze-drying to prepare a flexible polyvinyl alcohol-polyurethane sponge; Furthermore, the mass ratio of polyethylene glycol to hexamethylene diisocyanate (HDI) in S1 is 1:2-3; Further, the stirring temperature in S1 is 80-95°C, and the stirring time is 1-3 h; Further, the molecular weight of the polyethylene glycol in S1 is 500-5000; Further, the hydrophilic chain extender in S2 is dimethylol propionic acid; Further, the molar ratio of -OH in the dimethylol propionic acid to -NCO in the isocyanate-terminated polyurethane prepolymer in S2 is 0.1-0.9:1; Furthermore, the temperature for adding dimethylolpropionic acid to react in S2 is 80-90°C, the reaction time is 0.5-2 h, and after the reaction is completed, the temperature of the reaction system drops to 40-60°C; Further, the molar ratio of -OH in the hydroxyl-containing acrylate to -NCO in the isocyanate-terminated polyurethane prepolymer in S2 is 0.1-0.9:1; Further, the reaction time of adding the hydroxyl-containing acrylate in S2 is 3 h; Further, the hydroxyl-containing acrylate in S2 is selected from any one of hydroxyethyl acrylate (HEA), hydroxypropyl acrylate (HPA), hydroxyethyl methacrylate (HEMA) or pentaerythritol triacrylate (PETA); Further, the solid content of the polyurethane aqueous solution in S2 is 5-10%; Furthermore, the volume ratio of the polyvinyl alcohol aqueous solution to the polyurethane aqueous solution in S3 is 1 to 10:1; Further, the irradiation dose in S3 is 5 to 50 kGy; Further, the irradiation light in S3 is selected from any one of a high-energy electron accelerator, a cobalt source, X-rays or ultraviolet light; Furthermore, the freezing molding temperature in S3 is -30 to -15°C; the freezing molding time is 6 to 24 hours; Furthermore, the freeze-drying time in S3 is 24 to 48 hours.

[0007] A flexible polyvinyl alcohol-polyurethane sponge is prepared by the above preparation method.

[0008] A flexible polyvinyl alcohol-polyurethane sponge is used in the fields of biomedicine and tissue engineering.

[0009] Compared with the prior art, the present invention solves the problem that the mechanical properties and safety performance of the flexible polyvinyl alcohol-polyurethane sponge are insufficient, and the specific beneficial effects are: 1. Formation of a three-dimensional cross-linked network structure with high cross-linking density: The present invention utilizes -OH in hydroxyl-containing acrylate and -NCO in isocyanate-terminated polyurethane prepolymer to undergo nucleophilic addition reaction, thereby introducing C=C groups with radiation cross-linking sensitization into the polyurethane structure to prepare vinyl functionalized polyurethane; a polyvinyl alcohol-polyurethane sponge is prepared by radiation cross-linking method. During the irradiation process, polyvinyl alcohol and polyurethane absorb energy, resulting in the rupture of some covalent bonds and the generation of free radicals, which undergo cross-linking reactions. The introduction of C=C in polyurethane has a high electron cloud density of its π bond, which is easily attacked by electrophilic reagents, and the sensitivity of the polymer to radiation cross-linking can be enhanced through addition reaction. A dense three-dimensional cross-linked network structure is formed by cross-linking reaction with reactive groups (such as hydroxyl, amino, etc.) in polyvinyl alcohol and polyurethane.

[0010] 2. Excellent mechanical properties: The present invention achieves effective regulation of the degree of internal crosslinking of polyvinyl alcohol-polyurethane sponge by regulating the irradiation dose and the content of carbon-carbon double bonds (C=C). As the number of C=C introduced increases, the internal crosslinking reaction of the polyvinyl alcohol-polyurethane sponge is further promoted, the network structure of the polymer is enhanced, the mobility of the polymer chain is restricted, and the pore structure of the sponge is made more compact and uniform, thereby greatly improving the mechanical properties of the polyvinyl alcohol-polyurethane sponge. In addition, as the irradiation dose increases, the crosslinking effect of C=C and the synergistic effect of the free radicals generated by radiation promote the linking and twisting rearrangement of the polyurethane chain segments, thereby giving the polyvinyl alcohol-polyurethane sponge excellent flexibility and ductility.

[0011] 3. Safety and environmental protection: The present invention prepares polyvinyl alcohol-polyurethane sponge by using radiation cross-linking method. The preparation process does not rely on chemical catalysts, avoids the residue of harmful substances, ensures the non-toxic and environmentally friendly characteristics of the material, successfully avoids the problem of using toxic catalysts in traditional preparation methods, and significantly improves the application safety of polyvinyl alcohol-polyurethane sponge in the medical field. At the same time, polyvinyl alcohol itself has good biocompatibility and biodegradability, which not only improves the mechanical properties and stability of sponge materials, but also makes it more suitable for fields with strict requirements on safety and environmental protection, such as biomedicine, tissue engineering and other fields, which meets the development needs of green materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A synthetic route for vinyl-functionalized polyurethanes; Figure 2 This is the mechanism diagram of sensitized cross-linking reaction. DETAILED DESCRIPTION

[0013] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0014] Example 1. S1: 10.0 g of PEG with a molecular weight of 1000 and 3.4 g of HDI were added into a reaction bottle and reacted at 90°C for 2 h to prepare an isocyanate-terminated polyurethane prepolymer; S2: 0.7 g DMPA was added to the isocyanate-terminated polyurethane prepolymer, and the reaction was carried out at 90°C for 1.5 h. After the reaction, the temperature of the reaction system was lowered to 50°C, and 1.2 g HEA was added to react for 3 h. Finally, 0.4 g TEA was added for neutralization reaction to prepare vinyl functionalized polyurethane, and the vinyl functionalized polyurethane was dispersed into a polyurethane aqueous solution with a solid content of 10%; S3: Weigh 10 g of polyvinyl alcohol solid and add it to 90 g of water. Gradually heat it to 90°C and continue stirring for 2 h to completely dissolve it, thereby obtaining a polyvinyl alcohol aqueous solution with a mass fraction of 10%. The polyvinyl alcohol aqueous solution and the polyurethane aqueous solution prepared in S2 were mixed in a volume ratio of 1:1, and the mixed solution was poured into a mold with a size of 10×10 cm. The solution thickness was controlled to be 5 mm, and the mixed solution was irradiated with an electron beam dose of 30 kGy. After the irradiation, the mixed solution was placed in a -20°C environment and frozen for 12 h to form it. After taking it out, it was freeze-dried for 24 h to prepare a flexible polyvinyl alcohol-polyurethane sponge.

[0015] like Figure 1The synthetic route of vinyl functionalized polyurethane is shown in the figure, in which OCN-R1-NCO is diisocyanate, HO-R2-OH is a chain extender, and R3-OH is a hydroxyl-containing acrylate, wherein R1 and R2 are respectively C3-C12 hydrocarbon groups, R3 is a hydrocarbon group with one or more terminal double bond structures, and n is a natural number of 3-12; in the synthetic process, the present invention introduces a C=C group having a radiation cross-linking sensitization effect into the polyurethane structure through an addition reaction between -OH in the hydroxyl-containing acrylate and -NCO in the diisocyanate, thereby preparing a vinyl functionalized polyurethane, such as Figure 2 This is the mechanism diagram of sensitized cross-linking reaction.

[0016] Embodiment 2: The difference between this embodiment and embodiment 1 is that the volume ratio of the polyvinyl alcohol aqueous solution and the polyurethane aqueous solution in S3 is 9:1, and the other preparation steps and conditions are the same as those in embodiment 1.

[0017] Embodiment 3: The difference between this embodiment and embodiment 1 is that the dose of electron beam irradiation on the mixed solution in S3 is 20 kGy.

[0018] Embodiment 4: S1: 10.0 g of PEG with a molecular weight of 1000 and 3.5 g of HDI were added into a reaction bottle and reacted at 90 °C for 2 h to prepare an isocyanate-terminated polyurethane prepolymer; S2: 0.9 g DMPA was added to the isocyanate-terminated polyurethane prepolymer, and the reaction was carried out at 85°C for 1 h. After the reaction, the temperature of the reaction system was lowered to 50°C, and 0.7 g HEA was added to react for 3 h. Finally, 0.6 g TEA was added for neutralization reaction to prepare vinyl functionalized polyurethane, and the vinyl functionalized polyurethane was dispersed into a polyurethane aqueous solution with a solid content of 10%; S3: Weigh 10 g of polyvinyl alcohol solid and add it to 90 g of water. Gradually heat it to 90°C and continue stirring for 2 h to completely dissolve it, thereby obtaining a polyvinyl alcohol aqueous solution with a mass fraction of 10%. The polyvinyl alcohol aqueous solution and the polyurethane aqueous solution prepared in S2 were mixed in a volume ratio of 1:1, and the solution thickness was controlled to be 5 mm. The mixed solution was irradiated with an electron beam dose of 30 kGy. After the irradiation, the mixed solution was placed in a -20°C environment and frozen for 12 h to form it. After taking it out, it was freeze-dried for 24 h to prepare a flexible polyvinyl alcohol-polyurethane sponge.

[0019] Embodiment 5: S1: 10.0 g of PEG with a molecular weight of 1000 and 3.7 g of HDI were added into a reaction bottle and reacted at 90 °C for 2 h to prepare an isocyanate-terminated polyurethane prepolymer; S2: 0.7 g DMPA was added to the isocyanate-terminated polyurethane prepolymer, and the reaction was carried out at 90°C for 1 h. After the reaction, the temperature of the reaction system was lowered to 60°C, and 3.0 g PETA was added to react for 3 h. Finally, 0.4 g TEA was added for neutralization reaction to prepare vinyl functionalized polyurethane, and the vinyl functionalized polyurethane was dispersed into a polyurethane aqueous solution with a solid content of 10%; S3: Weigh 10 g of polyvinyl alcohol solid and add it to 90 g of water. Gradually heat it to 90°C and continue stirring for 2 h to completely dissolve it, thereby obtaining a polyvinyl alcohol aqueous solution with a mass fraction of 10%. The polyvinyl alcohol aqueous solution and the polyurethane aqueous solution prepared in S2 were mixed in a volume ratio of 1:1, and the mixed solution was poured into a mold with a size of 10×10 cm. The solution thickness was controlled to be 5 mm, and the mixed solution was irradiated with an electron beam dose of 30 kGy. After the irradiation, the mixed solution was placed in a -20°C environment and frozen for 12 h to form it. After taking it out, it was freeze-dried for 24 h to prepare a flexible polyvinyl alcohol-polyurethane sponge.

[0020] Comparative Example 1: S1: 10.0 g of PEG with a molecular weight of 1000 and 3.4 g of HDI were added into a reaction bottle and reacted at 90°C for 2 h to prepare an isocyanate-terminated polyurethane prepolymer; S2: 0.7 g DMPA was added to the isocyanate-terminated polyurethane prepolymer, and the reaction was carried out at 90°C for 1.5 h. After the reaction, the temperature of the reaction system was lowered to 50°C, and 1.2 g HEA was added to react for 3 h. Finally, 0.4 g TEA was added for neutralization reaction to prepare vinyl functionalized polyurethane, and the vinyl functionalized polyurethane was dispersed into a polyurethane aqueous solution with a solid content of 10%; S3: The polyurethane aqueous solution prepared in S2 was mixed with water in a volume ratio of 1:1, and the mixed solution was poured into a mold with a size of 10×10 cm. The solution thickness was controlled to be 5 mm, and the mixed solution was irradiated with an electron beam dose of 30 kGy. After the irradiation, the mixed solution was placed in a -20℃ environment and frozen for 12 h to form a shape. After taking it out, it was freeze-dried for 24 h to prepare a polyurethane sponge.

[0021] Comparative Example 2: 10 g of polyvinyl alcohol solid was weighed and added into 90 g of water. The solution was gradually heated to 90 °C and stirred for 2 h to completely dissolve the solid, thereby obtaining a polyvinyl alcohol aqueous solution with a mass fraction of 10%. The polyvinyl alcohol aqueous solution was mixed with water in a volume ratio of 1:1, and the mixed solution was poured into a mold with a size of 10×10 cm. The thickness of the solution was controlled to be 5 mm, and the mixed solution was irradiated with an electron beam at a dose of 30 kGy. After the irradiation, the mixed solution was placed in a -20 °C environment and frozen for 12 h to form the mold. After the mold was taken out, it was freeze-dried for 24 h to prepare a polyvinyl alcohol sponge.

[0022] Tensile properties test: According to the national standard GB / T 6344-2008, the samples prepared in Examples 1-5 and Comparative Examples 1-2 were cut into dumbbell shapes and subjected to a tensile property test on a testing machine, with the tensile speed set to 50 mm / min.

[0023] Water absorption performance test: The samples prepared in Examples 1-5 and Comparative Examples 1-2 were dried and weighed as m1, and then the samples were completely immersed in deionized water, taken out after immersion for 1 hour, and weighed again as m2. The water absorption rate was calculated according to the following formula: Water absorption rate = (m2-m1) / m1*100%.

[0024] The following table shows the performance results of the flexible polyvinyl alcohol-polyurethane sponges prepared in Examples 1-5, the polyurethane sponges prepared in Comparative Example 1, and the polyvinyl alcohol sponges prepared in Comparative Example 2. It can be seen from the data in the table that the flexible polyvinyl alcohol-polyurethane sponges prepared in Examples 1-5 retain the excellent elongation at break of the polyurethane sponge, while retaining the excellent tensile strength of the polyvinyl alcohol sponge, improving the shortcomings of the pure polyurethane sponge in terms of tensile strength and the shortcomings of the pure polyvinyl alcohol sponge in terms of elongation at break. This is mainly due to the fact that the hydroxyl-containing acrylate structure added in Examples 1-5 contains -OH and C=C double bonds, and the C=C double bonds are successfully introduced into the polyurethane structure through the nucleophilic addition reaction of -OH with the -NCO that has not been completely reacted after chain extension. During the irradiation process, polyvinyl alcohol and polyurethane absorb energy, resulting in the breaking of some covalent bonds and the generation of free radicals. These free radicals undergo cross-linking reactions to form a dense network structure and optimize mechanical properties.

[0025] It can be seen from the results of Example 1 and Example 2 that by changing the volume ratio of polyvinyl alcohol and polyurethane, the overall tensile strength of the material increases slightly due to the excessive content of polyvinyl alcohol, but the flexibility decreases significantly. This is because the polyurethane content is reduced and an effective flexible phase cannot be formed. At the same time, the hydrogen bonding between polyvinyl alcohols is enhanced, making it difficult for the molecular chain to slip, limiting the ductility of the material. It can be seen from the results of Example 1 and Example 3 in the table that with the increase of the irradiation dose, the cross-linking effect of C=C and the synergistic effect of the free radicals generated by radiation promote the linking and twisting rearrangement of the polyurethane chain segments, thereby giving the polyvinyl alcohol-polyurethane sponge excellent tensile strength. It can be seen from the results of Example 1 and Example 4 that in Example 4, due to the increase in the content of the chain extender, the tensile strength of the material decreases. This is because the amount of the chain extender and the hydroxy-containing acrylate are negatively correlated. The increase in the amount of the chain extender will lead to a decrease in the number of C=C introduced into the polymer structure, which reduces the intermolecular force, thereby reducing the tensile strength of the polyvinyl alcohol-polyurethane sponge. In addition, although an appropriate amount of chain extender can improve the linearity and crystallinity of the molecular chain and enhance the tensile strength of the material, an excessive amount may cause the molecular chain to be too short, which in turn reduces the tensile strength of the material and weakens its ability to withstand external forces. Example 5 uses PETA to replace HEA, increases the content of C=C, forms a denser network structure, and significantly improves the tensile strength; in addition, the hydrophilic carboxyl group in DMPA forms a hydrogen bond with water, thereby enhancing the adsorption capacity and retaining the excellent water absorption performance of the polyvinyl alcohol sponge.

[0026]

[0027] The present invention adopts the radiation cross-linking method to prepare a polyvinyl alcohol-polyurethane sponge with a dense three-dimensional cross-linked network structure. Through the dual regulation of the radiation dose and C=C, the degree of internal cross-linking of the polyvinyl alcohol-polyurethane sponge is effectively regulated, thereby giving the polyvinyl alcohol-polyurethane sponge excellent mechanical properties and ductility. In addition, the preparation process of the present invention does not rely on chemical catalysts, successfully avoiding the problem of using toxic catalysts in traditional preparation methods, significantly improving the application safety of polyvinyl alcohol-polyurethane sponges in the medical field, and meeting the development needs of green materials.

[0028] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0029] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a flexible polyvinyl alcohol-polyurethane sponge, characterized in that: The following steps are involved: S1: mixing polyethylene glycol and hexamethylene diisocyanate, stirring to react, and obtaining an isocyanate-terminated polyurethane prepolymer; S2: adding a hydrophilic chain extender to the isocyanate-terminated polyurethane prepolymer to react, lowering the temperature of the reaction system after the reaction is completed, continuing to add a hydroxyl-containing acrylate to react, and finally adding triethylamine to neutralize to prepare a vinyl-functionalized waterborne polyurethane, dispersing the vinyl-functionalized waterborne polyurethane in water to form a polyurethane aqueous solution; S3: The polyvinyl alcohol aqueous solution is mixed with the polyurethane aqueous solution prepared in S2, and the mixture is irradiated, followed by freeze molding, and finally freeze drying to prepare a flexible polyvinyl alcohol-polyurethane sponge.

2. The method for preparing a flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The molar ratio of polyethylene glycol to hexamethylene diisocyanate in S1 is 1:2-3; the stirring temperature is 80-95° C.; and the stirring time is 1-3 h.

3. The method for preparing the flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The molecular weight of the polyethylene glycol described in S1 is 500-5000.

4. The method for preparing a flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The hydrophilic chain extender in S2 is dimethylol propionic acid.

5. The method for preparing the flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The molar ratio of -OH in the dimethylolpropionic acid to -NCO in the isocyanate-terminated polyurethane prepolymer in S2 is 0.1~0.9:1; the temperature for adding dimethylolpropionic acid to react is 80~90°C, the reaction time is 0.5~2 h, and after the reaction is completed, the temperature of the reaction system drops to 40~60°C.

6. The method for preparing a flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The molar ratio of -OH in the hydroxyl-containing acrylate to -NCO in the isocyanate-terminated polyurethane prepolymer in S2 is 0.1-0.9:1; the reaction time of adding the hydroxyl-containing acrylate is 3 h; the hydroxyl-containing acrylate is selected from any one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or pentaerythritol triacrylate; the solid content of the polyurethane aqueous solution is 5-10%.

7. The method for preparing a flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The volume ratio of the polyvinyl alcohol aqueous solution to the polyurethane aqueous solution in S3 is 1-10:

1.

8. The method for preparing a flexible polyvinyl alcohol-polyurethane sponge according to claim 1, characterized in that: The irradiation dose in S3 is 5~50 kGy; the irradiation light is selected from any one of a high-energy electron accelerator, a cobalt source, X-rays or ultraviolet light; the freezing molding temperature is -30~-15℃; the freezing molding time is 6~24 h; and the freeze-drying time is 24~48 h.

9. A flexible polyvinyl alcohol-polyurethane sponge, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. An application of a flexible polyvinyl alcohol-polyurethane sponge, characterized in that: Applied in the fields of biomedicine and tissue engineering.

Citation Information

Patent Citations

  • Method for preparing polyvinyl alcohol and polyurethane super absorbent sponge

    CN102827442A

  • Water-soluble sponge with density gradient and preparation method and application thereof

    CN112063008A

  • Polyurethane-polyacrylacid ester interpenetrating network polymer, preparation and use thereof

    CN101481443A

  • High molecular weight linear urethane acrylate prepolymer, dielectric elastomer and preparation

    CN114316174A

  • Water gel containing natural high molecule and its radiation preparing method

    CN1944495A

Cited By

  • Polyurethane sponge as well as preparation method and application thereof

    CN120484327A